The Uncannily Intimate in Guy Maddin’s Cowards Bend the Knee: An Aesthetics of the Suddenly Obscene - Anne COMBARNOUS (E-REA)
Taking as a point of departure the Freudian notion of the “Unheimlich” and Jacques Lacan’s theory on the “ex-timate,” this paper will focus on the symbolic materialisation of the intimate, as a reflection of the split identity of the subject, and of the subject’s negotiation of the castration complex. This will be considered in relationship with the specific aesthetics of the obscene Guy Maddin deploys in the first film of what he defined as his ‘autobiographic’ trilogy, Cowards Bend the Knee (2003), an aesthetics that raises the question of individual and artistic responsibility, as well as of the viewer’s own responsibility. The Lacanian notions of the vacuole and jouissance will be explored in terms of what may be seen as their interpretive representations in the film, together with Lacan’s interpretation of Freud’s Vorstellungrepräsentanz and the Un-begriff.